2014
DOI: 10.4049/jimmunol.1400859
|View full text |Cite
|
Sign up to set email alerts
|

NK Cells with KIR2DS2 Immunogenotype Have a Functional Activation Advantage To Efficiently Kill Glioblastoma and Prolong Animal Survival

Abstract: Glioblastomas (GBMs) are lethal brain cancers that are resistant to current therapies. We investigated the cytotoxicity of human allogeneic NK cells against patient-derived GBM in vitro and in vivo, as well as mechanisms mediating their efficacy. We demonstrate that KIR2DS2 immunogenotype NK cells were more potent killers, notwithstanding the absence of inhibitory killer Ig–like receptor (KIR)-HLA ligand mismatch. FACS-sorted and enriched KIR2DS2+ NK cell subpopulations retained significantly high levels of CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 54 publications
3
72
0
Order By: Relevance
“…Considering that NK-differentiated tumors are highly susceptible to chemotherapy, whereas their stem-like tumors are highly resistant, the combination of NK cell immunotherapy and chemotherapy may be effective in the treatment of GBM patients [10, 51, 52]. The most troubling outcome of GBM to overcome when considering therapies is the ability to deplete cytotoxic NK cells due to their immunosuppressive effect.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that NK-differentiated tumors are highly susceptible to chemotherapy, whereas their stem-like tumors are highly resistant, the combination of NK cell immunotherapy and chemotherapy may be effective in the treatment of GBM patients [10, 51, 52]. The most troubling outcome of GBM to overcome when considering therapies is the ability to deplete cytotoxic NK cells due to their immunosuppressive effect.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, much less is known about the activating KIR, although they have been shown to play a significant role in viral infections and cancer . The activating KIR, KIR2DS2, is of particular interest given its protective role in bone marrow and cord blood transplantation for various hematological malignancies and in glioblastoma models in vivo . In addition, KIR2DS2 has recently been shown to directly recognise viral helicase peptides in the context of HLA‐C and to be protective against chronic hepatitis C virus infection .…”
mentioning
confidence: 99%
“…We have previously demonstrated that NK cells infiltrating patient glioblastoma tumors highly express activating receptor NKG2D (43) and that NK cells derived from aKIRs KIR2DS4 þ and KIR2DS2 þ donors were more potent against glioblastoma stem-like cells (44). Thus, the specific association of KIR2DS4 Ã 00101 with HLA-C1 in the context of CMV seropositivity in glioblastoma patients but not healthy controls has intriguing implications for immune response, although the mechanisms underlying their association remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that NK cells infiltrating patient glioblastoma tumors highly express NKG2D (43) and that subsets derived from KIR2DS4 immunogenotype donors were more potent against glioblastoma stem-like cells (44). Therefore, we hypothesized that altered distribution of NK cells' KIR-HLA ligand interactions as a result of CMV infections may influence malignant progression of glioblastoma.…”
Section: Kir2ds4mentioning
confidence: 99%